An Overview of Parents' Knowledge About Accident Prevention in Toddler - Irdawati Irdawati; Jayanti Ramadhanni; Azizah Ridha Syaiful (Jurnal Berita Ilmu Keperawatan, 2023)
The World Health Organization (WHO) states that no less than 875,000 children under the age of 18 worldwide die from injuries. The results of the 2018 Basic Health Research reported that the national prevalence of injury was 9.2%, with the highest prevalence of injury occurring in the home and environment with a percentage of 44.7%. In Central Java province alone, the percentage of injury incidence is 9.3%, this figure is higher than the national average rate of injury. Toddler injuries can actually be prevented with good supervision from parents, but these parents must also have good knowledge about handling injuries to children. Objective: This study aims to determine the level of parental knowledge about Accident Prevention in Toddler in the Gambirsari Health Center Work Area Method: This research type is a descriptive analytic study. The group studied were parents in the Gambirsari Health Center Working Area who had toddlers (aged 1-3 years), this study will describe the description of mothers' knowledge about accident prevention in toddlers in the Gambirsari Health Center Surakarta Work Area. Results: Based on the results of this study it can be concluded that the research subjects have the most age in the age range of 26-35 years (59%), the subjects of this study have the highest percentage of types of education at the high school level (57%), the subjects in this study the most work as IRT or housewives (74%), the highest percentage of toddlers is male sex toddler (60%), and 61% of the subjects have more than 1 children. Conclusion: Questionnaire statements with the most incorrect answers were found in statement point number 34 of 67.3%